Research Progress in Traditional Applications, Phytochemistry, Pharmacology, and Safety Evaluation of Cynomorium songaricum - Jin Zhang; Xingyi Chen; Lu Han; Biao Ma; Mengting Tian; Changcai Bai; Ye Zhang (Molecules, 2024)
Cynomorium songaricum Rupr. (CSR) belongs to the family Cynomoriaceae. It is a perennial succulent parasitic herb with a reddish-brown coloration, predominantly submerged in sand and lacking chlorophyll. Traditionally, it has been used in ethnic medicine to treat various diseases, such as gastric ulcers, indigestion, bowel movements, and improving sexual function. To comprehensively collect CSR data, extensive literature searches were conducted using medical, ecological, and scientific databases such as Google Scholar, PubMed, Science Direct, Web of Science, and China National Knowledge Infrastructure (CNKI). This article summarizes and categorizes research on the uses, phytochemical characteristics, pharmacological activities, and toxicity of ethnic medicine, with the aim of establishing a solid foundation and proposing new avenues for exploring and developing potential applications of CSR. So far, a total of 98 compounds have been isolated and identified from CSR, including flavonoids, terpenes, steroids, and other compounds. It is worth noting that flavonoids and polysaccharides have significant antioxidant and anti-inflammatory properties. In addition, these compounds also show good application prospects in anti-tumor, antioxidant, anti-aging, anti-fatigue, anti-diabetes, and other aspects. Although extensive progress has been made in the basic research of CSR, further research is still needed to enhance the understanding of its mechanism of action and explore more unknown compounds. Our review indicates that CSR has broad prospects and deserves further research.